Numerical Modeling Based on The Finite Element Method by Fortran90 Software on Beam-Column Joint - Dermawan, Adi Susetyo; Ishak, Syarifuddin; Sunarwadi, Hadi Surya Wibawanto; Setiawan, Ichwan (UIN Sumatera Utara, 2025)
This research discusses the finite element modeling of flexural failure in beam-column joints subjected to monotonic loads. This research aims to model numerically based on the finite element method by Fortran90 software on beam-column joint. The analysis is conducted using two-dimensional finite element method with three sides (triangular). The method used is quantitative and experimental. Validation testing is carried out on beam-column joint specimens with beam dimensions of 15x20 cm and column dimensions of 20x20 cm (a length of 100 cm). The compressive strength of the beam-column joint is 21 MPa. The test was conducted with a loading pattern at the end of the beam at a height of 1 m from the column. The comparison between the calculations using laboratory testing and the finite element method shows very consistent results.